Aproximações possíveis (e necessárias) entre Inteligência Artificial e escola - Zylbersztajn, Moisés (2024)
It seems imperative that schools, like any other institution, consider the urgent challenge of understanding, preparing for and participating in the development of artificial intelligence (AI) applications that can contribute to the management of teaching and the improvement of learning. Through the analysis of documents, publications and recent studies, this dissertation seeks to bring school and AI closer together, based on: a. technical conceptualization of the development of this area of experimentation, presenting mathematical models that support machine learning; b. case studies of educational applications, which allow recognizing the potential of possible solutions based on AI and c. critical analysis of the historical implementation of technologies in Brazilian schools to serve as input for the reflection that is necessary at this time